Using Mask Reduces Respiratory Problems Among the Workers of Ship Breaking Industry - Ahmed, Khan Shakil; Saha, Sanjoy; Islam, Md Shofiqul Islam; Hasanuzzaman; Imtiaz, Masud; Islam, Serajul; Saha, Shib Prosad (Journal of Dhaka National Medical College & Hospital, 2016)
The cross-sectional study showed that using facial mask reduces respiratory problems among the workers of the ship breaking industry. The study was conducted at Shitakund, Chittagong. Total 150 respondents were selected. Majority of the workers were <30 years of age & worked 8 hours daily. Among 150 respondents, 96% (n=144) has no previous respiratory problems. But respiratory problems like nasal irritation, hoarseness of voice, cough without cold, sneeze, chest tightness etc. were developing day by day due to their current job. Most of the respondents were conscious about using facial masks. About 21% (n=30) of the respondents used masks from the time of joining at the ship breaking industry & almost all of them were stay out of any type of respiratory problems. Around 39% (n=56) and 17% (n=24) of the respondents started to use mask within 6 months and 1 year of their joining respectively. Approximately 13% (n=19) of the respondents started to use mask after 1 year of their joining. All most of the mask users felt better within few days of using mask. Their respiratory problems reduced gradually after using mask. Rest 10% (n=15) of the respondents did not use mask at any time of their duration of service and all of them have some sorts of respiratory problems. From the study it is evident that using mask reduces respiratory problems among the workers of ship breaking industry J. Dhaka National Med. Coll. Hos. 2016; 22 (02): 21-24